Rethinking maternal vaccination in the era of climate change - Nazli Hossain (Journal of the Pakistan Medical Association, 2025)
The phenomena of climate change is making its impact globally. Pakistan though not a major contributor for climate change, is suffering from both direct and indirect effects. The effects of floods in the province of Sindh in 2022, can still be witnessed. The recent floods in Punjab have caused massive displacements of masses. One of the indirect effects of the climate change is an increase in the number of vector-borne infectious diseases like hepatitis, malaria, dengue and Zika virus infections.1 These infections carry increased risk of maternal mortality and morbidity. Also seen are the increased reporting for typhoid and cholera cases.2 Can these infections be prevented? There are number of ways to acquire success for this cause.One of such means is vaccination during pregnancy. Continue...